Appropriate use of the fixed-dose, extended-release combination of naltrexone and bupropion as treatment for obesity in primary care - Ethan Lazarus (Obesity Pillars)
Background: Obesity is considered a chronic disease and is influenced by biological, environmental, and behavioral factors that can contribute to its progression. Although lifestyle changes are integral to treating obesity and maintaining a healthful weight, weight reduction from behavioral intervention alone is often insufficient because neurophysiologic factors may work against such changes in lifestyle and behavior. Research suggests that the mechanisms underlying food cravings and obesity overlap with dopaminergic signaling in the brain and pathways involved in addiction. As a result, patients who are differentially impacted by food cravings may have better outcomes with treatments targeting neural systems implicated in both homeostatic and hedonic food consumption or addictive behaviors. Methods: In this clinical review, we describe the safety and efficacy data for the fixed-dose, extended-release combination of naltrexone and bupropion (NB-ER) compared with its monotherapy constituents (naltrexone and bupropion), as well as discuss the appropriate use of NB-ER to treat patients with obesity. Results: NB-ER is approved for the treatment of patients with obesity, with studies showing that patients can achieve significant weight reduction compared with placebo when treatment is combined with a reduced-calorie diet and increased physical activity. Across NB-ER phase 3 trials, responders to treatment had a mean body weight reduction of 11.7 % at 56 weeks. Of note, the unique combination of naltrexone, an opioid receptor antagonist, and bupropion, a norepinephrine-dopamine reuptake inhibitor associated with stimulating pro-opiomelanocortin cells (POMC), in NB-ER may work together to target POMC cells to prevent endogenous negative feedback, thereby decreasing appetite and improving weight-related outcomes. Conclusions: Unlike monotherapy with its component drugs, NB-ER is optimized for the treatment of obesity. The appropriate use of NB-ER should consider the specific characteristics and adiposity-related complications of an individual.